Projek pembelajaran menggunakan teknologi pembuatan komik untuk mendukung proses pembelajaran sains kelas rendah - Sari, Novita; Sari, Yowanda Lutfita; Dora, Zelvi Sepebrian; Putra, Zetra Hainul (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2022)
The study aims to develop science comic to support student learning. The ADDIE model was the development model employed in this investigation. Five phase analysis, design, development, implementation, and evaluation make up the ADDIE model. The participants for this study were 8 elementary school students. The finding of this study indicated that those students could understand the contents of science topics on the developed comics. They could explain what they have learned on that comic. Besides, the students also had positive attitude towards comics as a media for learing sciences. Therefore, science comics have a great potential for students’ learning of science.